Answer:
1 + ln 2 - ln x
Step-by-step explanation:
ln ( 2e /x)
We know that ln ( a/b) = ln ( a) - ln (b)
ln (2e) - ln (x)
We also know that ln ( a*b) = ln a + ln b
ln ( 2) + ln e - ln x
We know that the ln e = 1
ln 2 + 1 - ln x
Changing the order
1 + ln 2 - ln x
Answer:
Cory is correct
Step-by-step explanation:
When you divide 3.9 by 0.52 the quotient is 7.5. 7.5 will round up to 8.
Answer:
Simplifying
T = C(9 + AB) * forB
Reorder the terms for easier multiplication:
T = C * forB(9 + AB)
Multiply C * forB
T = forBC(9 + AB)
T = (9 * forBC + AB * forBC)
Reorder the terms:
T = (forAB2C + 9forBC)
T = (forAB2C + 9forBC)
Solving
T = forAB2C + 9forBC
Solving for variable 'T'.
Move all terms containing T to the left, all other terms to the right.
Simplifying
T = forAB2C + 9forBC
Step-by-step explanation:
Simplifying
T = C(9 + AB) * forB
Reorder the terms for easier multiplication:
T = C * forB(9 + AB)
Multiply C * forB
T = forBC(9 + AB)
T = (9 * forBC + AB * forBC)
Reorder the terms:
So if you wanted the factored form (exg. 1*2*3*4=24)
then this is (5 times 5 times 7)
Answer:
4, 2, 9, 3. They all work out
Step-by-step explanation:
If you need more help just lemme know! :))